2016
DOI: 10.4137/bci.s36143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sterculia setigera Del. Stem Bark Extract on Hematological and Biochemical Parameters of Wistar Rats

Abstract: Africa is rich in a wide range of flora that are exploited as herbal medicines and remedies. Several diseases such as diabetes, diarrhea, dysentery and jaundice have been successfully managed using herbal medicines. Herbal decoctions or concoctions have been used as pain killers, antibiotics, and hematinics. This study evaluated the hematopoietic and biochemical properties of the stem bark of Sterculia setigera Del. in Wistar rats. Results showed that S. setigera decoction has copiously high tannin and cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Platelet is implicated in blood clotting and plays a crucial role in reducing blood loss and repair of vascular injury [96]. The significant increase in platelet concentration in the BPH control indicates that the disease condition can stimulate the biosynthesis of blood clotting factors [97,98]. Mean platelet volume (MPV) is a simple indicator of platelet size and has been known to be a marker of platelet activity.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet is implicated in blood clotting and plays a crucial role in reducing blood loss and repair of vascular injury [96]. The significant increase in platelet concentration in the BPH control indicates that the disease condition can stimulate the biosynthesis of blood clotting factors [97,98]. Mean platelet volume (MPV) is a simple indicator of platelet size and has been known to be a marker of platelet activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the non-significant difference in WBC count and its differentials between the treatment and control groups suggested that the administered doses did not interfere with the differentiation of haemopoietic stem cells into these parameters. The significant effect on red blood cell differentials indicated that the extract affected the process of erythropoiesis probably by the phytochemicals interfering with the secretion and/or activity of erythropoietin (Zaruwa et al, 2016;Ojatula, 2019). Diminished levels of mean platelet volume and procalcitonin could probably be due to presence of toxic phytochemicals that interfere with the functioning of thrombopoietin or cause inflammation of the bowel (Mwale et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the non-significant difference in WBC count and its differentials between the treatment and control groups suggested that the administered doses did not interfere with the differentiation of haemopoietic stem cells into these parameters. The significant effect on red blood cell differentials indicated that the extract affected the process of erythropoiesis probably by the phytochemicals interfering with the secretion and/or activity of erythropoietin ( Awe and Banjoko, 2013 ; Mugisha et al, 2014 ; Zaruwa et al, 2016 ). Diminished levels of mean platelet volume and procalcitonin could probably be due to presence of toxic phytochemicals that interfere with the functioning of thrombopoietin or cause inflammation of the bowel ( Mwale et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%